Poor Renal and Cardiovascular Outcomes in Patients with Biopsy-Proven Diabetic Nephropathy - Yiyun Wang; Ting Zhou; Qiming Zhang; Yang Fei; Ze Li; Shiqi Li; Li He; Qunzi Zhang; Yang Dong; Ying Fan; Niansong Wang (Karger Publishers, 2020)
Background: Despite the high mortality of cardiovascular disease (CVD) in diabetic patients with renal injury, few studies have compared cardiovascular characteristics and outcomes between patients with diabetic nephropathy (DN) and non-diabetic renal disease (NDRD). Methods: A total of 326 type 2 diabetes mellitus patients with renal biopsy were assigned to DN and NDRD groups. Echocardiography and Doppler ultrasound were performed to evaluate left ventricular hypertrophy (LVH) and peripheral atherosclerosis disease (PAD). Renal and cardiovascular survival rates were compared between the DN and NDRD groups by Kaplan-Meier analysis. Risk factors for renal and cardiovascular events in DN patients were identified by a Cox proportional hazards model. Results: In total, 179 patients entered the DN group (54.9%) and 147 made up the NDRD group (45.1%). The presence of diabetic retinopathy, family history of diabetes, and dependence on insulin therapy were associated with the presence of DN. DN patients had more CVD with more severe LVH and PAD. Poorer renal (log-rank χ2 = 26.534, p < 0.001) and cardiovascular (log-rank χ2 = 16.257, p < 0.001) prognoses were seen in the DN group. DR (HR 1.539, 95% CI 1.332-1.842), eGFR (HR 0.943, 95% CI 0.919-0.961), and 24-h proteinuria (HR 1.211, 95% CI 1.132-1.387) were identified as risk factors for renal endpoints. Age (HR 1.672, 95% CI 1.487-1.821), HbA1C (HR 1.398, 95% CI 1.197-1.876), and 24-h proteinuria (HR 1.453, 95% CI 1.289-1.672) were associated with cardiovascular endpoints. Conclusion: Patients with DN had more severe CVD along with poorer renal and cardiovascular prognoses than those with NDRD.